Fabrication of photodiodes based on graphene oxide (GO) doped lanthanum hexaboride (LaB6) nanocomposites - Yalcin, Mesut; Al-Sehemi, Abdullah G.; Erol, Ibrahim; Aksu, Mecit; Tillayev, Sanjar; Dere, Aysegul; Yakuphanog, Fahrettin (Elsevier Science Sa, 2024)
GO-doped LaB6 nanocomposite-based Al/p-Si/GO:LaB6/Al photodiodes were fabricated for the study. The electrical properties of the fabricated photodiodes were subjected to current-voltage and capacitance-voltage measurements. The ideality factors, barrier heights and series resistance values of photodiodes were calculated and compared using the Cheung-Cheung and Norde methods approaches. The lowest ideality factor values were calculated to be 4.75, 4.00 and 9.21 in the samples doped with GO at 1 %, 5 % and 10 %, respectively, and the highest barrier height values were calculated from the Norde function to be 0.75, 0.64 and 0.75 eV, respectively Additionally, the responsivity (R) and detectivity (D) values of the diodes were calculated. The R values of 1 %, 3 % and % 5 doped diodes were calculated as 2153, 6001 and 2042 mA/W at, 100 mW/cm(2), respectively. The D* values of 1 %, 3 % and % 5 doped diodes are calculated as 1.38 x 10(11), 3.85 x 10(11) and 1.31 x 10(11) Jones at 100 mW/cm(2), respectively. The interface state (Nss) of 1 %, 3 % and % 5 doped diodes were calculated as 2 x 10(13), 1.25 x 10(13) and 1.06 x 10(13)eV(-1) cm(-2), at 100 mW/cm(2), respectively. It can be concluded that the diodes produced in this study have potential for use in optoelectronic applications.
Keywords: Photodiode; GO; Ideality factor; Barrier height; Nanocomposite; LaB6